2023
DOI: 10.1002/jso.27304
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal neoplasms—A practical guide

Abstract: Appendiceal neoplasms (ANs) are a diverse group of pathologies that range from benign to malignant with widely varying prognoses. This article serves as an overview of the practical approach to evaluating and managing a patient with AN by reviewing the current literature and guidelines to provide a framework for the management of these nuanced pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 73 publications
(180 reference statements)
0
6
0
Order By: Relevance
“…In previous studies, several risk factors for potential appendiceal malignancy were reported: age ≥ 50 years, atypical symptoms, presence of appendiceal phlegmon [ 19 ] or dilatation of the appendix [ 25 ] in radiological findings, immunosuppressive therapy including the use of steroids [ 19 , 34 ], absence of leucocytosis [ 25 ], and elevated CRP ≥ 54 mg/l [ 15 ]. Furthermore, female sex [ 28 ], ASA score ≥ 2, Crohn’s disease, anaemia on admission [ 15 , 19 ] and a history of previous malignancy [ 19 ] were found to be risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, several risk factors for potential appendiceal malignancy were reported: age ≥ 50 years, atypical symptoms, presence of appendiceal phlegmon [ 19 ] or dilatation of the appendix [ 25 ] in radiological findings, immunosuppressive therapy including the use of steroids [ 19 , 34 ], absence of leucocytosis [ 25 ], and elevated CRP ≥ 54 mg/l [ 15 ]. Furthermore, female sex [ 28 ], ASA score ≥ 2, Crohn’s disease, anaemia on admission [ 15 , 19 ] and a history of previous malignancy [ 19 ] were found to be risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of sessile serrated adenomas is estimated in one out of 1100 appendectomy specimens and the majority is found incidentally [ 41 ]. It is postulated that these lesions reveal in contrast to colorectal serrated lesions high rates of KRAS and lower rates of BRAF 500 mutations [ 34 ]. Serrated lesions of the appendix are limited to the muscularis mucosae and lamina propria, so that a complete resection for treatment is sufficient as performed in the underlying investigation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendiceal sessile serrated polyps are precursor adenomatous lesions proximal to the muscularis mucosa and lamina propria with malignant potential, have different histopathological features compared to colorectal serrated polyps, and undergo malignant transformation through different pathways with the conventional 'adenoma-carcinoma sequence' [20]. In addition, colonoscopic examination is recommended in patients with appendix sessile serrated lesions since the incidence of synchronous colorectal lesions is approximately four times higher compared to the overall population [21].…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal tumors are frequently identified incidentally during radiological examinations or abdominal surgery, with these procedures often being prompted by tumor-induced acute appendicitis. Accurate preoperative diagnosis is challenging and is typically confirmed by pathological analysis after resection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%